Application of AI in Education - Eka Putri, Elza; Mawardi, Mawardi; Warsah, Idi; Istan, Muhammad; Apriani, Eka (Corolla International Conference, 2024)
Nowadays, technology is developing very rapidly to support human tasks in life. One of them is the educational aspect. Currently technology creates products in the form of artificial intelligence. Alternatively, artificial intelligence is a system that is as close as possible to human intelligence and is embedded in devices to become an artificial intelligence tool. This tool is useful in the world of education because it allows searching for various forms of knowledge quickly and accurately and can be used anytime and anywhere. Data analysis that is usually difficult for humans is also possible. This tool can be used individually or in internal groups depending on the user's goals, thereby enabling AI technology to support the world of education effectively and efficiently. The purpose of this study is to outline how artificial intelligence (AI) is affecting schooling. In this study, a descriptive qualitative research methodology was employed. This approach is used to explain how AI is being used in education. This article's primary sources include literature, scientific journals, and web news about research issues. In order to form a conclusion, the data gathering approach involves reading, evaluating, and documenting a variety of relevant literature, scientific journals, and internet news sources. These are then filtered and placed within a theoretical framework. The study's findings demonstrate the enormous potential for improving educational efficacy and efficiency through the use of AI. Nevertheless, there are drawbacks to the application of AI in educational activities as well. As long as AI is applied carefully and effectively integrated into learning systems, it has the potential to be a priceless instrument for enhancing educational learning in the long run.